International Meniscus Reconstruction Experts Forum (IMREF) 2015 Consensus Statement on the Practice of Meniscal Allograft Transplantation. (April 2017) - Getgood, Alan; LaPrade, Robert F.; Verdonk, Peter; Gersoff, Wayne; Cole, Brian; Spalding, Tim; ,
Meniscal allograft transplantation (MAT) has become relatively commonplace in specialized sport medicine practice for the treatment of patients with a symptomatic knee after the loss of a functional meniscus. The technique has evolved since the 1980s, and long-term results continue to improve. However, there still remains significant variation in how MAT is performed, and as such, there remains opportunity for outcome and graft survivorship to be optimized. The purpose of this article was to develop a consensus statement on the practice of MAT from key opinion leaders who are members of the International Meniscus Reconstruction Experts Forum so that a more standardized approach to the indications, surgical technique, and postoperative care could be outlined with the goal of ultimately improving patient outcomes.